Aromatization Is Not Required for the Facilitation of Appetitive Sexual Behaviors in Ovariectomized Rats Treated With Estradiol and Testosterone - Jones, Sherri Lee; Rosenbaum, Stephanie; Gardner Gregory, James; Pfaus, James G. (Frontiers in Neuroscience, 2019)
Testosterone can be safely and effectively administered to estrogen-treated post-menopausal women experiencing hypoactive sexual desire. However, in the United States and Canada, although it is often administered off-label, testosterone co-administered with estradiol is not a federally approved treatment for sexual arousal/desire disorder, partly because its mechanism is poorly understood. One possible mechanism involves the aromatization of testosterone to estradiol. In an animal model, the administration of testosterone propionate (TP) given in combination with estradiol benzoate (EB) significantly increases sexually appetitive behaviors (i.e., solicitations and hops/darts) in ovariectomized (OVX) Long-Evans rats, compared to those treated with EB-alone. The goal of current study was to test whether blocking aromatization of testosterone to estradiol would disrupt the facilitation of sexual behaviors in OVX Long-Evans rats, and to determine group differences in Fos immunoreactivity within brain regions involved in sexual motivation and reward. Groups of sexually experienced OVX Long-Evans rats were treated with EB alone, EB+TP, or EB+TP and the aromatase inhibitor Fadrozole (EB+TP+FAD). Females treated with EB+TP+FAD displayed significantly more hops and darts, solicitations and lordosis magnitudes when compared to EB-alone females. Furthermore, TP, administered with or without FAD, induced the activation of Fos-immunoreactivity in brain areas implicated in sexual motivation and reward including the medial preoptic area, ventrolateral division of the ventromedial nucleus of the hypothalamus, the nucleus accumbens core, and the prefrontal cortex. These results suggest that aromatization may not be necessary for TP to enhance female sexual behavior and that EB+TP may act via androgenic pathways to increase the sensitivity of response to male-related cues, to induce female sexual desire.